A Comprehensive Review of the 1H-MRS Metabolite Spectrum in Autism Spectrum Disorder - Ford, Talitha C.; Crewther, David P. (Frontiers in Molecular Neuroscience, 2016)
Neuroimaging studies of neuropsychiatric behaviour biomarkers across spectrum disorders are typically based on diagnosis, thus failing to account for the heterogeneity of multi-dimensional spectrum disorders such as autism (ASD). Control group trait phenotypes are also seldom reported. Proton magnetic resonance spectroscopy (1H-MRS) measures the abundance of neurochemicals such as neurotransmitters and metabolites and hence can probe disorder phenotypes at clinical and sub-clinical levels. This detailed review summarises and critiques the current 1H-MRS research in ASD. The literature reports reduced N-acetylaspartate (NAA), glutamate and glutamine (Glx), gamma-aminobutyric acid (GABA), creatine and choline, and increased glutamate for children with ASD. Adult studies are few and results are inconclusive. Overall, the literature has several limitations arising from differences in 1H-MRS methodology and sample demographics. We argue that more consistent methods and greater emphasis on phenotype studies will advance understanding of underlying cortical metabolite disturbance in ASD, and the detection, diagnosis and treatment of ASD and other multi-dimensional psychiatric disorders.